Fan coil units - Price, Mike (TM (Chartered Institution of Building Services Engineers) ;, 2008)
Fan coil unit equipment has evolved steadily over the past few decades into a highly developed and effective means of providing air conditioning for a building. As with any technology there is the potential for serious problems if products are applied or installed incorrectly, thus making professional guidance essential. Recent legislation concerning energy reduction and carbon emissions further highlights the importance of correct design, installation, commissioning and maintenance to achieve efficient air conditioning and avoid energy waste. This Technical Memorandum sets out to describe all aspects of fan coil unit technology and provides manufacturers, designers, site personnel and operators a comprehensive guide. --